2021
DOI: 10.1515/opag-2021-0218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light spectrum on growth, development, and mineral contents of okra (Abelmoschus esculentus L.)

Abstract: Influence of the light spectrum on growth, development, and nutrients contents of okra was studied by growing okra (Abelmoschus esculentus L.) under three different LED-based irradiations defined by their peak wavelength at 455.45 ± 1.80 nm (B455), 522.27 ± 1.46 nm (G522), and 635.03 ± 1.33 nm (R635), respectively in the blue, green, and red regions of the visible spectrum. The photosynthetic photon flux density (PPFD) of 200 μmol m−2 s−1 was provided by the LEDs for 18 h daily. Leaves macronutrients and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The differential effects of PPFD and DLI on the mineral nutrient uptake exemplify that other lighting conditions such as light quality could have some effect on the uptake and allocation of specific dietary minerals. For instance, in the study with okra ( Abelmoschus esculentus L.), red light at 635 nm enhanced the accumulations of Ca and Mg while the highest N content was found in the plants grown under green light and blue light, respectively at 522 nm and 455 nm ( Degni et al., 2021 ). The effects of light intensity, quality, photoperiod and DLI on dietary mineral accumulation and the mechanisms involved are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The differential effects of PPFD and DLI on the mineral nutrient uptake exemplify that other lighting conditions such as light quality could have some effect on the uptake and allocation of specific dietary minerals. For instance, in the study with okra ( Abelmoschus esculentus L.), red light at 635 nm enhanced the accumulations of Ca and Mg while the highest N content was found in the plants grown under green light and blue light, respectively at 522 nm and 455 nm ( Degni et al., 2021 ). The effects of light intensity, quality, photoperiod and DLI on dietary mineral accumulation and the mechanisms involved are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in leaf area is one of the most important physiological parameters used to estimate the effective photosynthetic rates per unit area. For example, it has been reported that the largest leaf area is typically produced under blue LED illumination [15,103]. Note that a large leaf area allows a higher light-plant interception [37].…”
Section: Effect Of Led On Physiologymentioning
confidence: 99%
“…italica) cultivated under combined red and blue light (R/B = 1: 4), the amount of Ca, Mg, P, S, B, Cu, Fe, Mn, Mo, and Zn were increased (Kopsell et al, 2014). In a study by Degni et al (2021) on okra (Abelmoschus esculentus L.), results showed that red light increased absorption of Ca, P, and Mn, and blue light improved N content. Lettuce grown under recycled hydroponic subjected to combination of light quality (red + blue) increased the amount of nitrate (NO 3 − ) and nitrite (NO 2 − ) contents (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%